The impact of economic growth, money supply and exchange on inflation rate in Malaysia / Siti Nur Atiqah Mohamad Kherruldin - Mohamad Kherruldin, Siti Nur Atiqah (Faculty of Business and Management, 2017)
The aim of this study is to determine the relationships between economic growths, money supply, and exchange rate as independent variables that would effect to the inflation rate as dependent variable. The researcher has investigated how those of the variables would be effect on the inflation rate especially in Malaysia economic by using the annual basis data from year 1986 to 2015. There have three variables that have been taken as independent variable of this study. The name of the chosen variables is economic growths, money supply and exchange rate. The researcher interested to study in the relationship between this variable and inflation rate because to indicate the change of trends in the economy.